Growth of champa fruit under agroecological conditions of Miraflores, Boyacá, Colombia - Balaguera-López, Helber Enrique; Herrera Arevalo, Anibal; Cortes-Moreno, Daniel (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to analyze the growth of champa fruit (Campomanesia lineatifolia) as a function of growing‑degree days (GDD) in the municipality of Miraflores, in Boyacá, Colombia. Thirty trees were selected at random, and 100 flowers in full bloom were marked in each tree. From the 26th day after flowering until harvest, 10 samples were taken every 15 days to determine the fruit parameters and growth rate. Temperature was recorded to calculate the GDD. From flowering until harvest, 1,489.1 GDD were accumulated over 145 days. Dry and fresh matter mass of pulp, seed, and total fruit were fitted to a logistic growth model, and three growth stages (S1, S2 and S3) were defined. In the S1, growth was slow, and the relative growth remained nearly stable, whereas the absolute growth rate (AGR) increased slowly. In the S2, maximum growth was observed. In the S3, which corresponds to maturation, dry mass increased gradually, and the AGR decreased, while the fresh pulp and total mass did not cease to increase. The polar and equatorial diameters increased linearly, while the volume followed an exponential model. Champa fruit show a simple sigmoid growth curve.